Educate, assist, cure: organizational experiences and institutional configuration during the formation of Santiago del Estero State between the latest XIX and beginning of XX centuries (Papeles, 2023)
The following essay is an approach to the historical reconstruction of organizational forms (institutions, associations, councils, agencies, among others) linked to assistance, education and health that were formed in the context of state modernization in the province of Santiago del Estero between the late nineteenth and early twentieth centuries. These institutions (associations of varying degrees and types) were progressively shaping the public scene as well as incorporating themselves as a piece of the incipient administrative structure of the State; at the same time that they gave an account of the manifestations of the social question of the time.
Keywords: Santiago del Estero; State; Hygienism; Assistance; Education